Pengaruh Persepsi Harga, Endorser, dan E-WOM terhadap Minat Beli Skintific di Cilandak Jakarta Selatan - Ekasari, Silvia; Surip, Ngadino (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: Therefore, this study aims to find out the perception of price, celebrity endorsers and online promotions in influencing buying interest mediated by electronic word of mouth in Skintific Skincare in Cilandak, South Jakarta.Methodology/approach: The method used in this study is a verifiable descriptive method with a quantitative approach. The data used is primary data, namely by distributing questionnaires to respondents using the Convenience Sampling technique.Results/findings: The results of the study show that price perception, celebrity endorsers, and online promotions have a positive and significant effect on E-WOM. Price perception and E-WOM also directly have a positive effect on buying interest, while celebrity endorsers and online promotions do not. Indirectly, E-WOM is able to mediate the influence of price perception, celebrity endorsers, and online promotions on buying interest significantly.Conclusions: Research shows that price perception, celebrity endorser, and online promotion have a significant positive influence on E-WOM. Good price perception drives consumer satisfaction, while celebrity endorser strengthens product image, and online promotion facilitates information dissemination.Limitations: The study is limited to Skintific Skincare products, thus results may not generalize to other product categories. Future research should consider broader product categories to enhance the applicability of the findings.Contribution: This study enriches the literature by incorporating E-WOM as a mediating variable, providing a comprehensive understanding of consumer purchase interest in a digital context and offering insights into effective marketing strategies for local Skincare brands.